Differential Effect of Three Macrolide Antibiotics on Cardiac Pathology and Electrophysiology in a Myocardial Infarction Rat Model: Influence on Sodium Nav1.5 Channel Expression - Noha E. Farag; Mohamed K. El-Kherbetawy; Hussein M. Ismail; Ahmed M. Abdelrady; Eman A. Toraih; Walid Kamal Abdelbasset; Rehab M. Lashine; Mohammed EL-dosoky; Sally Yussef Abed; Khalid M. Ibraheem; Manal S. Fawzy; Sawsan A. Zaitone (MDPI AG, 2021)
Macrolides were reported to have cardiotoxic effects presented mainly by electrocardiogram (ECG) changes with increased risk in cardiac patients. We aimed to determine the impact of three macrolides, azithromycin, clarithromycin and erythromycin, on cardiac electrophysiology, cardiac enzyme activities, histopathological changes, and sodium voltage-gated alpha subunit 5 (Nav1.5) channel expression. We used eight experimental groups of male albino rats: vehicle, azithromycin (100 mg/kg), clarithromycin (100 mg/kg), erythromycin (100 mg/kg), MI + vehicle, MI + azithromycin (100 mg/kg), MI + clarithromycin (100 mg/kg) and MI + erythromycin (100 mg/kg); each group received chronic oral doses of the vehicle/drugs for seven weeks. ECG abnormalities and elevated serum cardiac enzymes were observed particularly in rats with AMI compared to healthy rats. Microscopic examination revealed elevated pathology scores for rats treated with clarithromycin in both experiments following treatment with erythromycin in healthy rats. Although rats with MI did not show further elevations in fibrosis score on treatment with macrolides, they produced significant fibrosis in healthy rats. Downregulation of cardiac Nav1.5 transcript was observed following macrolides treatment in both groups (healthy rats and rats with MI). In conclusion, the current findings suggested the potential cardiotoxic effects of chronic doses of macrolide antibiotics in rats with MI as manifested by abnormal ECG changes and pathological findings in addition to downregulation of Nav1.5 channels. Furthermore, in the current dose ranges, azithromycin produced the least toxicity compared to clarithromycin and erythromycin.